(untitled) (Sains Humanika, 2018)
This study is aimed to obtaining preliminary data for the need for guidance in the process of identifying netball player talent below 12 years in elementary school. Inconsistent player performance is a concern in this study. Experience of the coaches also plays an important role in forming a solid team of players. The questionnaire was developed to obtain feedback from the trainer on the selection process of the player. The results show that 90% of the coaches agree that there is a reference to the selection of players during the preparation of school netball teams. However, the findings show that 100% of the trainers strongly agree about the necessary course of netball in helping to provide knowledge and skills. It shows that existing references need to be improved with more effective guidelines. Furthermore, there is a relationship between the coaches’ experience of 50% less than five (5) years with the required knowledge and skills of player selection. Therefore, the researcher proposes the development of a guideline for netball player selection process who is under 12-years old to simplify tasks of the coaches.